Holiday effects in the South African futures market - C. F. Smit; E. V.D.M. Smit (South African Journal of Business Management, 1998)
International and local research in share markets offered evidence of a holiday effect. Pre-holiday mean returns are significantly higher than on other trading days. The holiday effect cannot be separated from the weekend effect, as holidays which fall on Fridays and Mondays also influence the weekend analysis. Both these effects exist in their own right. Research on international futures markets supports the existence of a holiday effect. The present study investigates the holiday effect on daily returns of the All Gold Near Futures contract, the All Industrial Near Futures contract and the All Share Near Futures contract in the South African futures market. A distinction is made between pre-holidays, post-holidays and non-holidays. None of the near futures contracts exhibit a significant holiday effect, although signs of a holiday effect are present. It is further shown that the month-end effect is not strongly influenced by the holiday effect. It is also concluded that the pre-holiday effects are not large enough to be exploited on an on-going basis in the South African futures market.
Keywords: 650